(untitled) (Boletin Médico de Postgrado, 2020)
The goal of this study is determine the risk factors for sexual abuse of pediatric patients admitted to the Hospital Pediátrico Dr. Agustin Zubillaga during the period December 2018-January 2019. A cross-sectional descriptive study was performed with a sample of 20 patients with an average age of 7.3 years and an age range between 2 years and 6 years old; 55% were females. In regards to individual, familial and community risk factors, the results show a predominance of single parent families (55%), 75% of mothers did not work and were economically dependent on the father, 60% of fathers were unemployed and 65% of patients lived in overcrowded conditions with lack of privacy. The results of this study allowed identification of risk factors in this group of patients in order to generate recommendations to manage this terrible issue that affects an increasing number of children.